Utilization of phytohormones for successful crop production under environmental stress conditions - Faiq, Mohammad Hussain; Noori, Mohammad Safar (Journal of Scientific Agriculture, 2021)
Stress is an external factor that exerts a detrimental effect on overall growth of a plant. Environmental stress is a serious threat for sustainable crop production, and a main cause for food insecurity. Agricultural crops are exposed to a variety of environmental stresses including extreme temperatures and unfavorable chemical and physical soil conditions. Drought stress adversely affects some physiological and biochemical processes in plants, including transpiration, translocation of assimilates and nutrient metabolism. Salinity stress is responsible for loss of turgor, reduction in growth, wilting, leaf abscission, reduction in photosynthesis and respiration, loss of cellular integrity, tissue necrosis and finally death of the plant. Drought and salinity stress negatively affects the growth and yield of crop plants more than all the other stresses combined. Cold stress affects cellular components and metabolism, and temperature extremes impose stresses of variable severity that depend on the intensity and duration of the stress. Many approaches are being used to alleviate the deleterious effects of environmental stresses on successful agricultural crops production in recent years. Application of phytohormones (Abscisic acid, Indole-3-Aacetic Acid, Jasmonic acid and salicylic acid) is one of the curative measures to mitigate the environmental stresses in agricultural crops. Phytohormones play a significant role in enhancing stress tolerance and therefore, reduce the yield loss in crop plants. In this paper, the impacts of environmental stresses on productivity and physiological activities of crop plants, and the effective role of some phytohormones in alleviation of environmental stresses have been reviewed.